Strength assessment of stiffened blast walls in offshore installations under explosions. (3rd July 2016) - Sohn, Jung Min; Kim, Sang Jin; Seo, Jung Kwan; Kim, Bong Ju; Paik, Jeom Kee
Abstract : Offshore installations are exposed to hydrocarbon explosions and/or fire accidents. Especially, explosions lead to serious damages to human, safety, and environment. To minimise and prevent the damage from explosions, blast walls are generally installed in oil and gas production structures. Typical blast walls are classified into flat, corrugated, and stiffened types. Among them, corrugated blast walls are frequently used for reasons such as construction, cost, and energy absorption. However, it has been known that a corrugated type of blast wall buckles between the web and flange under the explosion loads, and loses its stiffness. It means that the buckling phenomenon of a blast wall is closely related to the structural strength. This study investigates on the structural characteristics of a blast wall under quasi-static and dynamic (explosion) loads with or without a flat-plated stiffener. Finally, it can be concluded that the flat type of stiffeners are located at the buckling region to delay the buckling and improve the strength of blast walls.